Effects Of Varying Arc Angles And Poles Numbers On Force Characteristics Of Switched Reluctance (SR) Actuator - Yusri, I; Md Ghazaly, Mariam; Rahmat, Mohd Fua'ad; Chong, Shin Horng; Ranom, Rahifa; Abdullah, Zulkeflee (IJENS Publishers, 2016)
-